2016
DOI: 10.1136/heartjnl-2015-309069
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular arrhythmias and sudden cardiac death in adults with congenital heart disease

Abstract: Remarkable gains in survival have led to an unprecedented number of adults with congenital heart disease. Arrhythmias collectively comprise the most common complication encountered. Recognising the unique issues and challenges involved in managing arrhythmias in adults with congenital heart disease and the consequential decisions surrounding sudden death prevention, expert societies have proposed evidence-based recommendations. On the whole, acute ventricular arrhythmias are managed according to general cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 34 publications
0
30
0
1
Order By: Relevance
“…Cardiac arrhythmias are the leading cause of sudden death (Khairy, 2016;Priori et al, 2016;Saffitz and Corradi, 2016), and many talks focused on the molecular mechanisms underlying such arrhythmias. Examining a post-injury paradigm that occurs in many human tissues, Catherine Lipovsky (from Stacey Rentschler's lab, Washington University in St Louis, USA) found that transient activation of Notch1 in the adult mouse myocardium leads to sinus bradycardia (low heart rate) and slow atrial conduction velocity, suggesting a direct role for Notch activation in long-term maintenance of the atrial electrical phenotype.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…Cardiac arrhythmias are the leading cause of sudden death (Khairy, 2016;Priori et al, 2016;Saffitz and Corradi, 2016), and many talks focused on the molecular mechanisms underlying such arrhythmias. Examining a post-injury paradigm that occurs in many human tissues, Catherine Lipovsky (from Stacey Rentschler's lab, Washington University in St Louis, USA) found that transient activation of Notch1 in the adult mouse myocardium leads to sinus bradycardia (low heart rate) and slow atrial conduction velocity, suggesting a direct role for Notch activation in long-term maintenance of the atrial electrical phenotype.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…For more accurate identification of risk markers, one solution to dealing with effect modification is to perform lesion-specific analyses (20). This was addressed in part by Oliver et al's online supplement, which presents survival curves separately for individual types of CHD (3).…”
mentioning
confidence: 99%
“…Pediatrist ya da pediatrik kardiyologların hastalarını erişkinlik döneminde erişkin kardiyoloji ya da kalp damar cerrahisi anabilim dallarına yönlendirmeleri ve bu konuda gerekli bilgilendirmeyi yapmaları, tıbbi ve etik sorumlulukları arasındadır (5). Konjenital ya da edinsel kalp hastalığı olan kadının, hastalığın olası komplikasyonlarından korunması ikincil korumadır (6).…”
unclassified